Dynamic simulation test of a model of ecological system security for a coastal tourist city. (September 2019) - Lu, Xiaoli; Yao, Shimeng; Fu, Guo; Lv, Xiaofei; Mao, Yanan
Abstract: This paper presents a model of an ecological security system for coastal tourism cities and performs a dynamic simulation test of it. Data for the coastal city of Dalian, China, covering the period 2001 to 2015, were used to simulate the city's ecological security from 2016 to 2030. This confirmed the validity of the model, which had a low average error. Variables were chosen to simulate a number of different scenarios. Considering the number of tourists, tourism income, the index of tourism resources and marine pollution, the low-carbon environment scenario was shown to be the healthiest, with a high level of investment in environmental protection and resource consumption and a low outcome in terms of industry development. The simulation results for the three scenarios showed that more capital and high technology should be invested to improve the treatment of marine pollution in Dalian, which can reduce its negative impact on coastal areas and create a conducive environment to attract tourists. The research provides a systems approach to evaluate potential socio-economic influences on the ecological security systems of coastal tourism cities, and to provide information useful for destination management. Highlights: Proposes an ecological security system for a coastal tourism city with three sub-systems. Develops a systems dynamics model to perform a simulation test. Predicts future changes in coastal tourism urban ecological security. The low-carbon environment scenario is found to be the healthiest. Capital and technology are the key factors needed to decrease pollution.